2015
DOI: 10.1097/brs.0000000000000816
|View full text |Cite
|
Sign up to set email alerts
|

Patient-, Procedure-, and Hospital-Related Risk Factors of Allogeneic and Autologous Blood Transfusion in Pediatric Spinal Fusion Surgery in the United States

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…No significant variations in overall or subgroup compliance rates were shown in subgroups of age, sex, type of insurance, and diagnosis, though there were significant differences in AP compliance by race. Findings of racial disparity in pediatric surgical care are not unique; 1,6,7 reasons for this disparity in AP compliance are unclear and warrant further study. As substratification with specific patient comorbidities was not conducted in this study, it may be that there were specific clinical concerns or indications requiring prolonged antibiotic use beyond the recommended < 24-hour duration in guidelines.…”
Section: Discussionmentioning
confidence: 95%
“…No significant variations in overall or subgroup compliance rates were shown in subgroups of age, sex, type of insurance, and diagnosis, though there were significant differences in AP compliance by race. Findings of racial disparity in pediatric surgical care are not unique; 1,6,7 reasons for this disparity in AP compliance are unclear and warrant further study. As substratification with specific patient comorbidities was not conducted in this study, it may be that there were specific clinical concerns or indications requiring prolonged antibiotic use beyond the recommended < 24-hour duration in guidelines.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the reported differences in transfusion practices between races in adults in major surgery and the paucity of information in pediatrics, we set out to study potential racial disparities among patients undergoing pediatric scoliosis surgery at our institution to determine if a measurable difference existed that may suggest an increased transfusion risk in minorities. Our retrospective review of medical records allowed for reliable identification of Black and White patients, however “Other” races were not consistently identified and therefore were grouped together for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the inconsistent methodology in measuring intraoperative estimated blood loss, 1 surrogate that has been used in this population is blood transfusion requirement . Conservative studies estimate that at least 25% of pediatric spine surgeries require intraoperative blood transfusion . Minimizing blood transfusion is beneficial as transfusions have been associated in adult and pediatric literature with increased morbidity, including risk of surgical site infections (SSI), longer hospitalizations, and increased cost …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with blood loss in PSF for scoliosis or kyphosis have been investigated mostly in retrospective studies . These studies have implicated the following patient and surgical risk factors for blood loss: Cobb angle >50°, female gender, African American race, anemia, known bleeding disorders, abnormal coagulation profiles, neuromuscular scoliosis, operative time, posterior lumbar fusion, number of levels fused, and use of Ponte osteotomies . Ryan and colleagues found that children with scoliosis have a high prevalence of abnormalities in screening coagulation laboratory tests obtained preoperatively compared with healthy patients, primarily the prothrombin time .…”
Section: Introductionmentioning
confidence: 99%